Digital economy and regional economic resilience: a dual-test of industrial structure mediation and institutional environment moderation - Qi, Peipei; Nassar Waked, Hayyan; Yao, Niaoer; Wang, Qi (Frontiers in Physics, 2026)
IntroductionAs a crucial driver of growth under the new development pattern, the digital economy requires in-depth examination regarding its role in enhancing regional economic resilience.MethodsUsing China’s provincial panel data from 2011 to 2023, this study investigates the mechanisms through which the digital economy affects regional economic resilience by employing fixed-effects models, mediation tests, and interaction tests.ResultThe findings are as follows: First, the development of the digital economy significantly strengthens regional economic resilience, with particularly prominent performance in the dimensions of transformation and development capabilities. Second, this effect is transmitted through the dual mediating mechanisms of rationalization and upgrading of the industrial structure. Third, the positive effect of the digital economy displays a clear institutional dependence, and can materialize fully only when strong policy support and a high level of marketization coexist. Finally, the impact of the digital economy exhibits significant regional heterogeneity: the effect is most pronounced in the Central region, while it has not yet fully emerged in the western region.DiscussionThis research establishes a theoretical framework linking the digital economy, industrial structure, and economic resilience; reveals the mediating role of industrial structure optimization and the moderating role of institutional conditions; enriches the theoretical understanding of how the digital economy shapes economic resilience; and provides practical insights for fostering a new pattern of regional economic resilience.